PTH-066 Cholangioscopic management of proximally migrated biliary stent using a novel through the cholangioscope snare. (June 2019) - Kotha, Sreelakshmi; Berry, Philip; Webster, George; Wong, Terry
Abstract : Migration of biliary stent occurs in 5–10% of cases. However, proximal migration of pigtail stents is rare. Retrieval of these stents can be challenging and requires utilisation of various endoscopic grasping devices. With increasing use of ERCP and biliary stents this is being encountered more frequently. Most stents can be retrieved with conventional grasping devices like stent grabbers or biopsy forceps. However, some case may require the use of novel through the cholangioscope devices. We present a 37-year-old lady who presented with choledocholithiasis and 4 conventional ERCPs were not successful in clearing the CBD stones. At spy glass cholangiscopy we discovered a proximally migrated biliary stent. This video demonstrates a novel technique to retrieve the migrated biliary stent.